2014
DOI: 10.1105/tpc.114.130773
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Alternative Splicing in Zea mays: Landscape and Genetic Regulation  

Abstract: Alternative splicing enhances transcriptome diversity in all eukaryotes and plays a role in plant tissue identity and stress adaptation. To catalog new maize (Zea mays) transcripts and identify genomic loci that regulate alternative splicing, we analyzed over 90 RNA-seq libraries from maize inbred lines B73 and Mo17, as well as Syn10 doubled haploid lines (progenies from B73 3 Mo17). Transcript discovery was augmented with publicly available data from 14 maize tissues, expanding the maize transcriptome by more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
181
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(210 citation statements)
references
References 55 publications
26
181
3
Order By: Relevance
“…Tissue-specific accumulation of metabolites, representing one of the main contributions to metabolite diversity, is of great interest to plant scientists (Schilmiller et al, 2010;Chan et al, 2011;Watanabe et al, 2013). Metabolic diversity between different tissues might arise from differences in spatial-temporal expression of genes (Kim et al, 2012;Thatcher et al, 2014) and in some cases by duplicate genes that display spatially or temporally distinct expression patterns (Toubiana et al, 2012;Matsuba et al, 2013). By comparing genetically controlled natural variation of PAs in different tissues at high resolution, we have shown that although coordinated genetic control across various tissues can be observed for some PAs, the majority of the loci were obtained in a tissue-specific manner (Supplemental Table 4), suggesting distinct regulation underlying the metabolic readout between tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue-specific accumulation of metabolites, representing one of the main contributions to metabolite diversity, is of great interest to plant scientists (Schilmiller et al, 2010;Chan et al, 2011;Watanabe et al, 2013). Metabolic diversity between different tissues might arise from differences in spatial-temporal expression of genes (Kim et al, 2012;Thatcher et al, 2014) and in some cases by duplicate genes that display spatially or temporally distinct expression patterns (Toubiana et al, 2012;Matsuba et al, 2013). By comparing genetically controlled natural variation of PAs in different tissues at high resolution, we have shown that although coordinated genetic control across various tissues can be observed for some PAs, the majority of the loci were obtained in a tissue-specific manner (Supplemental Table 4), suggesting distinct regulation underlying the metabolic readout between tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Novel transcripts were then filtered to remove lowabundance isoforms, which could be the result of sequencing processing intermediates or incorrect transcript assembly. Transcripts were required to have an average expression among four biological replicates of at least 1.3 fragments per kilobase per million reads (FPKM) in at least one stage and condition for ear, tassel, and leaf in order to optimize the tradeoff between false-positive and false-negative discoveries (Thatcher et al, 2014). Since many seed, endosperm, and embryo stages lacked biological replicates, the requirement for these tissues was an average of 1.3 FPKM in at least four biological replicates and/or consecutive developmental stages in at least one tissue.…”
Section: Discovery Of Novel Transcriptsmentioning
confidence: 99%
“…Genes involved in processes ranging from auxin biosynthesis to iron transport have tissue-specific alternative splicing patterns that affect both protein localization and function (Kriechbaumer et al, 2012;Li et al, 2013). Tissuespecific splicing patterns can also alter a transcript's sensitivity to regulation by microRNAs, such as the maize (Zea mays) SPX family, which produces miR827-sensitive isoforms that predominate in developing seedlings, while insensitive isoforms dominate other tissues (Thatcher et al, 2014). Gene expression changes in splicing factors also play key roles in guiding tissuespecific developmental processes, including seed development, where the U2AF splicing factor ROUGH ENDOSPERM3 has been shown to be involved in mediating the interaction between the embryo and endosperm (Fouquet et al, 2011).…”
mentioning
confidence: 99%
“…Previously, using the homology based mapping approach and expressed sequence tags (ESTs) representing the functional transcripts, we identified a total of 941 AS genes in Brachypodium distachyon, a model temperate grass (Sablok et al, 2011;Walters et al, 2013). Previous reports on the identification and prevalence of the alternative splicing events in rice (Campbell et al, 2006;Wang and Brendel, 2006), sorghum (Panahi et al, 2014), and maize (Thatcher et al, 2014) have shown the functional diversity changes through EST/RNA-seq approaches. Recently we also reported our efforts in identification of AS genes in rice (both japonica and indica), maize, and sorgum (Min et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide identification and physiological implications of AS have been reported in plant species including A. thaliana (Filichkin et al, 2010;Zhang et al, 2010;Marquez et al, 2012;Syed et al, 2012), Oryza sativa (Wang and Brendel, 2006), Nelumbo nucifera (sacred lotus) (VanBuren et al, 2013), Vitis vinifera (Vitulo et al, 2014), Brachypodium distachyon (Sablok et al, 2011;Walters et al, 2013), Zea mays (maize), and Sorghum bicolor (sorghum) (Thatcher et al, 2014;Min et al, 2015). Approximately 60 -75% of AS events occur within the protein coding regions of mRNAs, resulting changes in binding properties, intracellular localization, protein stability, enzymatic, and signaling activities (Stamm et al, 2005).…”
Section: Introductionmentioning
confidence: 99%